2000
DOI: 10.1053/ejvs.1999.0991
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stent Design on Proximal Stent-graft Fixation in the Abdominal Aorta: an Experimental Study

Abstract: a sutured anastomosis fixates a graft better than any stent design tested. Hooks and barbs improve the fixation of self-expandable stents. Balloon dilatation of the proximal stent after deployment might increase fixation further. Balloon expandable stents seem to provide good fixation without the use of hooks and barbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 13 publications
7
133
1
1
Order By: Relevance
“…7 A number of factors hypothesized to affect device migration have been clinically investigated, including aortic neck diameter, length, and angulation; neck calcification and thrombus; neck enlargement; inadequate proximal and distal fixation length; and neck enlargement. [8][9][10] In-vitro 11 and in-vivo experimental studies, 12 as well as theoretical 13 and computational studies, [14][15][16][17][18][19] have been conducted to investigate the magnitude of the loads acting on endografts. These loads have been referred to as migration forces, displacement forces, or drag forces.…”
mentioning
confidence: 99%
“…7 A number of factors hypothesized to affect device migration have been clinically investigated, including aortic neck diameter, length, and angulation; neck calcification and thrombus; neck enlargement; inadequate proximal and distal fixation length; and neck enlargement. [8][9][10] In-vitro 11 and in-vivo experimental studies, 12 as well as theoretical 13 and computational studies, [14][15][16][17][18][19] have been conducted to investigate the magnitude of the loads acting on endografts. These loads have been referred to as migration forces, displacement forces, or drag forces.…”
mentioning
confidence: 99%
“…Our predicted displacement forces echo those of other CFD studies which report values in the range of 4 to 10 N, as shown in Table 3. Experimental studies have indicated that older generations of stent-grafts (prior to the use of large barbed suprarenal stents) can only resist displacement forces of 2.5 to 8.0 N [32][33][34].…”
Section: Clinical Relevancementioning
confidence: 99%
“…37. Graph comparing anchoring force (in Newtons) for various proximal fixation strategies for stent grafts, from references [32][33][34].…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…AAAs with problematic proximal neck-short (from 5 to 15 mm), conical or with a long enough but angulated one -were excluded from EVAR preserving classical stentgrafting indications criteria due to the problematic stentgraft fixation [2][3][4] . The basic types of fixation such as stent-graft self-expansion, barbs, hooks or suprarenal bare wire fixation in the more stable part of aorta are not adequate in these cases of proximal neck anatomy [5][6][7][8][9] . One possibility for providing successful stent-graft fixation is the use of associated surgery -external aortic banding 10 .…”
Section: Introductionmentioning
confidence: 99%